Pemberdayaan Orang Tua Siswa Dalam Meningkatkan Mutu Pembelajaran Di Sdn Sabranglor No. 78 Surakarta - Muryati, Muryati; Sumardjoko, Prof. Dr. Bambang Sumardjoko; Rohmah, MM, Dr. Wafrotur Rohmah, MM (2017)
This study have two aims to: 1) describe the role of parents in supporting the implementation of learning programs, 2) find a model of empowerment of parents in order to improve the quality of learning at SDN Sabranglor No. 78 Jebres, Surakarta. This research is qualitative research with etnography design. Data was collected by observation, interview, and documentation. Data analysis use interactive analysis are data reduction, data display and verification. The validity of the data using source triangulation. Results of this research there are two things about: 1) The role of parents in supporting the implementation of the learning program at SDN Sabranglor No. 78 Jebres carried out in the form of a financial role in the form of school funding; the role of infrastructure in the form of provision of transport, consumption, textbooks and teaching aids; the role of energy and skills in the form of donations of energy and expertise in various programs; the role of encouragement in the form of actively provide feedback and suggestions in the learning program, motivation to learn and help solve the problem of students. 2) Model of empowering parents to improve the quality of learning at SDN Sabranglor No. 78 Jebres through institutional of school board and mmunication through parents' visit to school and meeting of school program socialization.